The impact of hospital case volume on the outcomes after catheter ablation for atrial fibrillation according to the ablation technology. (26th April 2022) - Kanaoka, Koshiro; Nishida, Taku; Nishioka, Yuichi; Myojin, Tomoya; Kubo, Shinichiro; Soeda, Tsunenari; Okada, Katsuki; Noda, Tatsuya; Iwanaga, Yoshitaka; Miyamoto, Yoshihiro; Sakata, Yasushi; Imamura, Tomoaki; et al.
Abstract: Introduction: The appropriate hospital case volume for catheter ablation (CA) in patients with atrial fibrillation (AF) according to the ablation technology has not been fully examined. This study aimed to investigate the association between the hospital case volume for AF and periprocedural complications and AF recurrence. Methods: In this retrospective cohort study, we used data from the National Database of Health Insurance Claims and Specific Health Checkups, which covers almost all healthcare insurance claims data in Japan. We included patients with AF who underwent first‐time CA from April 2014 to March 2020. Using mixed‐effect logistic regression, we analyzed the effect of the annual case volume for AF ablation on acute periprocedural complications and 1‐year success rate off antiarrhythmic drugs according to the ablation technology (radiofrequency ablation or cryoballoon ablation). Results: Among 270 116 patients, 207 839 (77%) patients underwent radiofrequency ablation and 56 648 (21%) patients underwent cryoballoon ablation. Of all patients, acute complications occurred in 5411 (2.0%) patients, and the recurrence at 1 year was 71 511 (27%). In the radiofrequency ablation group, acute complications and 1‐year AF recurrence according to case volume decreased as the annual case volume increased to up to 150−200 cases/year. However, in the cryoballoon ablation group, these outcomes were similar regardless of the case volumes. Conclusion: The case‐volume effect was noted in the radiofrequency ablation group, but not in the cryoballoon ablation group. Our results may affect the selection of ablation technology, especially in smaller case‐volume hospitals.